2020
DOI: 10.1177/2514848620945315
|View full text |Cite
|
Sign up to set email alerts
|

How “wild” are hatchery salmon? Conservation policy and the contested framing of nature in Canada and the United States

Abstract: The idea of the Anthropocene presents a paradox for conservation: to restore and protect wild species and ecosystems, greater human intervention is required through efforts such as artificial propagation. This paradox is evident in efforts to conserve Pacific salmon. Salmon hatcheries produce millions of salmon to augment wild populations and sustain fishing industries, but emerging knowledge about salmon genomics has called into question the “wildness” of hatchery salmon. This article examines how the scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…behaviour and appearance) to technically-driven definitions (i.e. fish multiple generations removed from hatchery-origin relatives) (Berseth & Matthews, 2021;Harrison et al, 2019). In response, jurisdictions across the salmon stocking world are responding by (broadly):…”
Section: Aug Ht In a Los E-los E Par Adox?mentioning
confidence: 99%
See 3 more Smart Citations
“…behaviour and appearance) to technically-driven definitions (i.e. fish multiple generations removed from hatchery-origin relatives) (Berseth & Matthews, 2021;Harrison et al, 2019). In response, jurisdictions across the salmon stocking world are responding by (broadly):…”
Section: Aug Ht In a Los E-los E Par Adox?mentioning
confidence: 99%
“…behaviour and appearance) to technically‐driven definitions (i.e. fish multiple generations removed from hatchery‐origin relatives) (Berseth & Matthews, 2021; Harrison et al., 2019). In response, jurisdictions across the salmon stocking world are responding by (broadly): Reforming hatchery and genetic management plans to minimize the genetic risks by prioritizing and monitoring genetic diversity within stocked systems, though budgetary constraints remain a challenge (Mobrand et al., 2004; see example: Oregon Department of Fish and Wildlife, 2017, p. 10 Indicator 14(f)). Pursuing the production of more ‘wild‐type’ salmon through approaches such as captive habitat enrichment and hatchery reform. Curtailing or eliminating conservation stocking programs all together. …”
Section: Caught In a Lose‐lose Paradox?mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on the social aspects of hatcheries and stocking within the Alaskan context has often focused on economic aspects, such as the value of hatchery-reared fish to the Alaskan economy (Boyce et al 1993;Herrmann 1993;Pinkerton 1994). However, research elsewhere has found that social and cultural values and attitudes toward fish can be facilitated through hatchery programs (Harrison et al 2018) and that perceptions of the "wildness" or "artificiality" of salmon can be derived from paradoxes of policy (Berseth and Matthews 2020), relationships with food (Takahashi 2014), and technological approaches to conservation (see Meffe 1992;Maynard and Trial 2014). Currently, there is limited research exploring the human and policy dimensions of Alaska's salmon enhancement program (but see Eller 2018;Gould 2019;Crittenden 2021) or whether the program meets its stated objectives (Jahn 2020).…”
mentioning
confidence: 99%